Geert Mak: Jorwerd. The Death of the Village in Late Twentieth-Century Europe - Davidson, Alan E (Petits Propos Culinaires, 2024)
Geert Mak: Jorwerd. The Death of the Village in Late Twentieth-Century Europe: Harvill, 2000: ISBN 1-86046-803-9, 274 pp., p/b, £12.00.